2009
DOI: 10.1073/pnas.0812644106
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of ecological public goods

Abstract: The production, consumption, and exploitation of common resources ranging from extracellular products in microorganisms to global issues of climate change refer to public goods interactions. Individuals can cooperate and sustain common resources at some cost or defect and exploit the resources without contributing. This generates a conflict of interest, which characterizes social dilemmas: Individual selection favors defectors, but for the community, it is best if everybody cooperates. Traditional models of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
227
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(240 citation statements)
references
References 42 publications
12
227
1
Order By: Relevance
“…In liquid conditions, mutants that do not produce siderophores have, in fact, been shown to outcompete WT strains (5)(6)(7)(8). However, the limited spatial dispersal of public goods can challenge this picture and has been proposed as a general mechanism for explaining the maintenance of cooperation (8)(9)(10)(11)(12). When dispersal is limited, public good molecules tend to stay in the vicinity of the producing subpopulations, allowing them to benefit preferentially from their own production, and thus to balance the advantage of opportunistic nonproducing strains.…”
mentioning
confidence: 99%
“…In liquid conditions, mutants that do not produce siderophores have, in fact, been shown to outcompete WT strains (5)(6)(7)(8). However, the limited spatial dispersal of public goods can challenge this picture and has been proposed as a general mechanism for explaining the maintenance of cooperation (8)(9)(10)(11)(12). When dispersal is limited, public good molecules tend to stay in the vicinity of the producing subpopulations, allowing them to benefit preferentially from their own production, and thus to balance the advantage of opportunistic nonproducing strains.…”
mentioning
confidence: 99%
“…Inspired by the seminal paper introducing games on grids [18], evolutionary games on graphs and complex networks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have proven instrumental in raising the awareness of the fact that relaxing the simplification of well-mixed interactions may lead to qualitatively different results that are due to pattern formation and intricate organization of the competing strategies, which reveals itself in most unexpected ways. Specifically for the spatial public goods game [38,39], it has recently been shown that inhomogeneous player activities [40], appropriate partner selection [41,42], diversity [43][44][45], the critical mass [46], heterogeneous wealth distributions [47], the introduction of punishment [48,49] and reward [50], as well as both the joker [51] and the Matthew effect [52], can all substantially promote the evolution of public cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed by Hauert et al [10][11][12], small population densities favour cooperators. This is because the benefit that a single cooperator gets from its own investment is spread over fewer individuals, and thus may exceed its cost.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate potential coupling between ecological resilience and stability to freeloader invasion, we studied the behaviour of the Ecological Public Goods Game (EPGG) [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation